(untitled) (Web of Teachers: Inderscience Research, 2024)
This article is based on the fact that precedent names, as units of language and speech, are a linguistic and cultural process that occurs as a result of the communication of representatives of different languages, as a sum of the national-cultural worldview, national character, lifestyle and values of each people.